Asuhan Kebidanan Pada Ibu Nifas Di Rsud Dok II Jayapura Provinsi Papua - Melvina Kakyarmabin; Fauziah.F.Hernanto; Dewi Purwatiningsih (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
The purpose of the study was to provide continuous midwifery care (continuity of care) and to document SOAP notes for pregnant women, those giving birth, and those in the postpartum period. The method used the Varney management approach. The patient who was accompanied was Mrs. "T" at the Dok II Hospital in Jayapura City. The midwifery care provided to Mrs. "T" aged 33 years lasted ± 8 weeks. The first visit on 06-04-2022 found a diagnosis of a pregnant woman with GIVP2011 UK 37/38 weeks. The results of the anamnesis and physical examination found no problems. Based on the assessment of the Poedji Rochjati Score Card, the mother is included in the high-risk group with a score of 6. During pregnancy, the mother had 8 antenatal visits according to the standard schedule per trimester. The mother gave birth on May 6, 2022 at 20.05 WIB with a gestational age of 39 weeks. The delivery took place normally, the baby was born spontaneously assisted by a midwife, the baby cried, moved actively, was female, was immediately given IMD, birth weight 3,080 grams, body length 49 cm, APGAR score 8-9, placenta was born spontaneously complete, normal bleeding ± 200 cc, there was a second degree tear in the birth canal, the third and fourth stages were normal. The baby received eye ointment and Vit K after birth, and received Hb-0 immunization. The postpartum period was carried out 4 times with the results of the right breast lactation not producing breast milk, involution and lochia were normal. On the first postpartum visit, Mrs. "T" said there was a little pain in the stitches and on the next visit there were no complaints.